The Influence of Internet – Communication on Everyday Speech - Ildarovna Galiullina, Liana (2021)
The article deals with the problem of the reverse influence of the Internet and chat communication on the spoken language based on the "Language of scum" in the Russian-speaking Internet. Today, this problem is relevant, since the development of the Internet has contributed to the widespread use of slang among the younger generation. The Internet today is a source of information. But the speed and availability of communication between users made it possible to use the Internet not only as a cognitive tool, but also as a means of communication and entertainment. And virtual communication, which arose due to the rapid development of the network, gave rise to a special language - the language of virtual communication. The numerous chats, open forums and personal pages created on the network are the main ways of communication among young people. Over the years, a special language has developed in the programs - slang, the so-called language of Internet communication, in which users communicate with each other. And every day he actively penetrates into our daily life. This study is a kind of appeal not only for adolescents, but also for the adult population. I would like people to think about the fact that we need to protect our language and not succumb to the influence of slang when communicating on social networks. The practical significance of the work lies in the fact that the results of this study will be useful to students in order to preserve their native language.